(untitled) (Architecture Image Studies, 2021)
This paper attempts to explore the relationship between climate catastrophe and the globalised economy of late capitalism and the implication that the architectural profession has been complicit with the environmental failures of this system. The essay identifies a number of key authors who argue that late-capitalism is not only a significant factor in climate catastrophe but is also responsible for a fatalistic position of ‘no alternative’ which have weakened effective opposition and the creation of other possible futures. It is suggested that many of these critical positions fail to convince as they cannot effectively communicate what an alternative future might look like, and suggests that architects, using speculative techniques familiar to Science Fiction, could be uniquely situated to try and represent what these forms of otherness might be and authors can map out future possibilities. But, if this is to happen it requires a rethinking of what architecture is and what architects do and how architectural education needs to change to facilitate these transformations.